Insurance and flood risk reduction in Ghana: do insurers penalise homeowners who take precautionary measures?. (1st October 2016) - Antwi-Boasiako, Benjamin Addai
ABSTRACT: Today, many advocate insurance as a tool for coping with natural disasters. Beyond providing prompt financial relief to victims of disasters, insurance can also incentivise individuals to invest in preventive measures if insurers reward such efforts with reduced premiums. However, insurers might be unable to reward investments in precautionary measures with lower premiums if they are ill-informed about individual-level risks. Here, we explore how Ghanaian home insurers respond to investments in flood risk reduction by asking them to quote premiums for four identical buildings; two had investments in flood risk reduction, while the other two had none. We find that insurers did not reward investments in risk reduction, with some charging higher premiums for elevated buildings, suggesting they have interpreted such preventive measures as a sign of high flood risk. This failure to reward investments in precautionary measures may discourage insured homeowners from investing in risk reduction.